Screening for Iron Overload: Lessons from the HEmochromatosis and IRon Overload Screening (HEIRS) Study - Paul C Adams; James C Barton; Gordon D McLaren; Ronald T Acton; Mark Speechley; Christine E McLaren; David M Reboussin; Catherine Leiendecker-Foster; Emily L Harris; Beverly M Snively; Thomas Vogt; Phyliss Sholinsky; et al. (Canadian Journal of Gastroenterology)
BACKGROUND: The HEmochromatosis and IRon Overload Screening (HEIRS) Study provided data on a racially, ethnically and geographically diverse cohort of participants in North America screened from primary care populations.